27 Evaluating the Functional Differences at Genome, Transcriptome and Methylome Level between ARS-UCD1.2 and UMD 3.1 Bovine Reference Genomes. (21st September 2022) - Cánovas, Angela; Fonseca, Pablo A S; McKay, Stephanie D; Medrano, Juan F F
Abstract: Crossbred beef steers, n = 5, 140; 352 ± 5.45 kg initial body weight (BW) were used to evaluate chromium propionate supplementation to yearling steers in a commercial feedyard. Cattle were blocked by arrival date and initial BW and assigned randomly to pen within block; pens were randomly assigned to treatment within block. Treatments, replicated in 15 pens per treatment with 130 to 250 steers per pen, included: 1) control (CTL), 0 mg supplemental Cr/kg dietary dry matter (DM); 2) chromium (CR) 0.50 mg supplemental Cr/kg dietary DM (4.9 mg/d; chromium propionate; KemTRACE Chromium 0.4%, Kemin Industries, Des Moines, IA). Final BW, average daily gain (ADG) and gain efficiency (G:F) did not differ among treatments (P ≥ 0.26). Dry matter intake was greater for CR than CTL, 8.61 kg. vs. 8.49 kg, respectively (P = 0.03). Hot carcass weight (HCW), dressing percentage, ribeye area, and 12 th -rib-fat were not different for CTL or CR (P ≥ 0.12). The percentage of carcasses camera grading choice or better was greater (P = 0.04) for CR (51.2%) than CTL (48%), and the percentage of select carcasses was less (P = 0.01) for CR (41.5%) than CTL (45.5%). Yield grade distribution did not differ among treatments (P ≥ 0.26). There was no difference (P ≥ 0.36) in overall morbidity (7.75%), or total mortality (1.43%) between treatments. Steers fed CR had higher quality carcasses, and similar G:F and HCW to CTL.